Preliminary Study on the Cytoarchitecture of the Human Parabrachial/Kölliker-Fuse Complex, with Reference to Sudden Infant Death Syndrome and Sudden Intrauterine Unexplained Death - Lavezzi, Anna Maria; Ottaviani, Giulia; Ballabio, Gianmario; Rossi, Lino; Matturri, Luigi (Pediatric and developmental pathology, 2004)
The parabrachial/Kölliker-Fuse complex has been defined, in different animal species, to lie in the dorsolateral part of the pontine tegmentum and to be subdivided into three well-defined regions: the medial parabrachial nucleus, the lateral parabrachial nucleus, and the Kölliker-Fuse nucleus. Experimental studies have shown that the parabrachial/Kölliker-Fuse complex is involved in a variety of functional activities and above all plays an important role in respiratory modulation. In human brainstem, the cytoarchitecture and physiology of this complex have not yet been fully characterized. The aim of the present study was to examine fetal and infant human brainstems in order to define the precise morphology of the three nuclei of the parabrachial/Kölliker-Fuse complex, and to determine whether this nervous center shows morphologic alterations in sudden infant death syndrome (SIDS) and in sudden intrauterine unexplained death (SIUD). In serial sections of 31 brain-stems of subjects aged from 32 gestational wk to 10 months of life, we studied, by morphologic and morphometric analyses, the cytoarchitecture and the extension of the three nuclei of the parabrachial/Kölliker-Fuse complex. All the morphometric parameters were very similar in SIUD and SIDS cases to those of the respective control group, as shown by the absence of significant statistical differences between the two fetus and infant groups. We observed that the features of both the lateral and the medial parabrachial nuclei are largely consistent with those reported in experimental studies. In contrast, the Kölliker-Fuse nucleus appears to be more developed in human beings than in other animal species, showing a greater extension and a more complex structure, as well as subdivision into two subnuclei (compactus and dissipatus).